For a global education. A research-training project to integrate sustainable development and global citizenship - Anna Perazzone; Paola Ricchiardi; Federica Emanuel; Emanuela Maria Teresa Torre; Marco Davide Tonon (Firenze University Press, 2024)
Although Education for Sustainable Development (ESD) and Global Citizenship (GDEC) are proposed as complementary in educational policy documents, they are still perceived as interrelated fields but with specificities that tend to depower projects aimed at either domain. The research-training project presented aimed to develop awareness in teachers of different school levels of what ESD and GDEC share, and then proceed with associations to co-design educational programs on global competence. Surveys to assess the starting level and the effectiveness of the diverse interventions are included. The paper presents the outcomes related to teachers' perceptions (N=219) at the beginning of the training and students' global competence (N=4.426) before the start of the interventions in schools.   Per un'educazione globale. Una ricerca-formazione per integrare sviluppo sostenibile e cittadinanza globale. Sebbene l'Educazione alla Sviluppo Sostenibile (ESS) e alla Cittadinanza Globale (ECG) siano proposte come complementari nei documenti di politiche educative, sono ancora percepite come ambiti interrelati ma con specificità che tendono a depotenziare i progetti mirati all'uno o all'altro campo. Il progetto di ricerca-formazione presentato si propone di sviluppare negli insegnanti di diversi livelli scolastici consapevolezza su ciò che accomuna ESS e ECG, per poi procedere con associazioni ad una co-progettazione di percorsi didattici sulla competenza globale. Sono previste rilevazioni per valutare il livello iniziale e l'efficacia dei diversi interventi. Il contributo presenta gli esiti relativi alla percezione degli insegnanti (N=219) all'inizio del percorso formativo e alla competenza globale degli alunni (N=4.426) prima dell'avvio degli interventi nelle scuole.